2012
DOI: 10.1159/000341379
|View full text |Cite
|
Sign up to set email alerts
|

Low, Complex and Probably Reticulated Chromosome Evolution of Sciuromorpha (Rodentia) and Lagomorpha

Abstract: Lagomorpha (rabbits and pikas) and Sciuromorpha (squirrels) are grouped in the Glires superorder. Their chromosome diversification, since their separation from the eutherian mammalian common ancestor, was characterized by a low rate of chromosome rearrangements. Consequently, the structure of some chromosomes was either conserved or only slightly modified, making their comparison easy at the genus, family and even order level. Interspecific in situ hybridization (Zoo-FISH) largely corroborates classical cytoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…[ 22 , 23 ]). Although comparisons between human and rodent genomes using chromosome painting have had limited success, results in Sciuromorpha, Castorimorpha, and Anomaluromorpha showed that most of the ancestral eutherian syntenic associations were conserved [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, some rodents such as Myomorpha have experienced massive chromosomal rearrangements [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 , 23 ]). Although comparisons between human and rodent genomes using chromosome painting have had limited success, results in Sciuromorpha, Castorimorpha, and Anomaluromorpha showed that most of the ancestral eutherian syntenic associations were conserved [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. However, some rodents such as Myomorpha have experienced massive chromosomal rearrangements [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristic of the various karyotypes of Laonastes is the presence of very large chromosomes, obviously derived from multiple rearrangements, as demonstrated by the presence of up to eight fragments homologous to human chromosomes on a single chromosome. In these large chromosomes, no additional adjacent syntheny corresponds to those proposed for the ancestors of other rodents such as Glires, Sciuridae, or Muroidea (Romanenko et al 2006;Graphodatsky et al 2008;Sannier et al 2011;Beklemisheva et al 2011;Richard and Dutrillaux 2012). Interestingly, the size increase of some chromosomes was a tendency yet at work in the evolution of genus Laonastes: three of the six rearrangements differentiating the karyotypes of our specimens are tandem fusions increasing the size of pairs 3 and 4.…”
Section: Reconstruction Of the Karyotype Of Laonastes Common Ancestormentioning
confidence: 50%
“…The X chromosome is submetacentric in all species while the small Y chromosomes is acrocentric in Euxerus and metacentric in Xerus, both species of Geo sciurus and Spermophilopsis; the details are not known for Atlantoxerus. Differences in morphology of the Y chromosome most probably originate from the pericentric inversion which is the predominant drive of chromosomal change in squirrels (Richard and Dutrillaux 2012). Such differences provide little useful information for phylogenetic reconstructions of interrelationships in Sciuridae because of convergent and reverse rearrangements of the karyotype (Romanenko et al 2011, Richard andDutrillaux 2012).…”
Section: Chromosomesmentioning
confidence: 99%
“…Differences in morphology of the Y chromosome most probably originate from the pericentric inversion which is the predominant drive of chromosomal change in squirrels (Richard and Dutrillaux 2012). Such differences provide little useful information for phylogenetic reconstructions of interrelationships in Sciuridae because of convergent and reverse rearrangements of the karyotype (Romanenko et al 2011, Richard andDutrillaux 2012). Evidently, Xerini have retained a conservative karyotype which remains similar to the ancestral condition in squirrels (Li et al 2006, Beklemisheva et al 2011).…”
Section: Chromosomesmentioning
confidence: 99%